Response of Cucurbita spp. to tomato leaf curl New Delhi virus inoculation and identification of a dominant source of resistance in Cucurbita moschata. (30th September 2020) - Romero‐Masegosa, Jonathan; Martínez, Cecilia; Aguado, Encarnación; García, Alicia; Cebrián, Gustavo; Iglesias‐Moya, Jessica; Paris, Harry S.; Jamilena, Manuel
Abstract: Tomato leaf curl New Delhi virus is an emerging whitefly‐borne species of begomovirus in Mediterranean regions that poses a severe threat to cucurbit crops of the genus Cucurbita . Until now, only two sources of resistance have been identified in Cucurbita spp., these being PI604506 (cv. Large Cheese) and PI381814 (Indian landrace), both of C. moschata . The resistance of cv. Large Cheese is conferred by a single recessive gene located on chromosome 8. The objective of the present investigation was to screen for tomato leaf curl New Delhi virus (ToLCNDV) resistance among 105 accessions drawn from five species of Cucurbita and, if high resistance was found in any of them, determine the mode of inheritance. Screening was conducted using whitefly‐mediated inoculation on all 105 accessions. The accessions showing some resistance were further screened by mechanical inoculation as well as by quantitative PCR‐based diagnostics. The results showed that, overall, the accessions of C. pepo and C. maxima were the most susceptible, those of C. argyrosperma and C. ecuadorensis intermediate, and those of C. moschata most resistant to ToLCNDV. Only one accession of C. moschata, BSUAL‐252, originating from Japan, was highly resistant to ToLCNDV, showing no symptoms after either method of inoculation, and absence of virus accumulation. Upon crossing BSUAL‐252 with a susceptible accession of C. moschata, BSUAL‐265, the resistance was observed to be conferred by a single dominant gene. This gene is not linked to the genomic region on chromosome 8 where the locus of the previously identified recessive gene for ToLCNDV resistance resides. Abstract : The Cucurbita moschata BSUAL‐252 is a new source of resistance to ToLCNDV discovered in a massive screening of the genus, which will be useful to produce resistant lines in breeding programmes of Cucurbita species.